Pre-landing plans for Mars Oxygen In-Situ Resource Utilization Experiment (MOXIE) science operations. (March 2022) - McClean, John B.; Hoffman, Jeffrey A.; Hecht, Michael H.; Aboobaker, Asad M.; Araghi, Koorosh R.; Elangovan, S.; Graves, Christopher R.; Hartvigsen, Joseph J.; Hinterman, Eric D.; Liu, Andrew M.; Meyen, Forrest E.; Nasr, Maya; et al.
Abstract: The Mars Oxygen In-Situ Resource Utilization Experiment (MOXIE) is a technology demonstration on the NASA Mars 2020 Perseverance rover. MOXIE is capable of producing 6–10 g/h of oxygen via solid oxide electrolysis of atmospheric carbon dioxide. The Mars 2020 mission has allocated MOXIE a minimum of ten oxygen-producing runs, each with approximately 1 h of oxygen production. Before landing, operations were planned to meet MOXIE's five success criteria. Run structure, constraints, and thorough definition and validation processes were defined. Before producing oxygen for the first time, several checkouts were planned to verify functionality of MOXIE's major subsystems. MOXIE's first oxygen-producing run was planned to produce up to 6 g/h of oxygen for approximately 1 h and measure a conservative range of current and voltage at two inlet mass flow rates. The remaining oxygen-producing runs were planned to measure performance using the largest permissible range of current, voltage and inlet mass flow rate for a wide range of atmospheric densities. Runs were designed to be flexible, allowing modification as operational knowledge accumulates throughout the mission. Validation of runs using models and hardware has demonstrated that MOXIE is ready for surface operations.